Increasing Critical Thinking Competence Through the Podcast Method on the Material of Democratic Dynamics - Dwi Wiwik Nur Handayani (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2022)
The purpose of this study was to determine the use of the podcast method in improving critical thinking competence in the dynamics of democracy in Indonesia. This research is a qualitative research, with a descriptive method, taking class XI students of SMA Negeri 1 Pangkalpinang as the object of study. Data collection techniques using observation techniques, interviews, and documentation. The results of this study indicate that critical thinking competence can emerge through the podcast method in the matter of democratic dynamics. This study also found that podcasts are the preferred learning media and can lead students to a new and fun learning process, so that it is hoped that it will be able to bring out other competencies in students.